Tahlîlu Jaudati Bunûdi al-Ikhtiyârât al-Muta'addidah li Ta'lîmi 'Anâshiri al-Lughah al-'Arabiyyah - Maftuhati Maftuhati; Nihayatin Musyafa'ah; Silmi Maulidya (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2021)
This study aims to explore and determine the quality of test items including the validity and relevance of the Arabic language final exam questions in the form of multiple choice at MTs Halunuk Loksado. The method used is a descriptive method with a qualitative approach. Sources of data in this study consisted of two types, the first was primary data sources obtained from interviews. Second, secondary data sources from the documentation. Researchers collected data using structured interview techniques and documentation, then analyzed using Milles and Huberman analysis techniques. The results showed that the final examination items for grade eight of MTs Halunuk Loksado showed a fairly high validity.